Constitutional studies on the Borneo Agreement / Abdul Haqq Abd Razak … [et al.] - Abd Razak, Abdul Haqq; Abdul Rahim, Azizul Helmi; Jumaludin, Muhamad Firdaus; Abdul Hakim, Muhammad Muaz; Syed Muhamad, Syed Muhd Isa @ Ismat (2010)
This research is a study on the Borneo Agreement made during the formation of Malaysia. This study sets out to discover the reasons of the said agreement between Peninsular Malaysia and the State of Sabah and Sarawak. This is due to the fact that after more than 50 years of the formation, the relevancies of the agreement are being question. The agreement was made according to the responses from the citizen in the State of Sabah and Sarawak. Basically it is to safeguards their special rights and position. Thus all the special rights of the citizen in the State of Sabah and Sarawak have been adopted in the Federal Constitution. However, nowadays these special rights give bad effects on the State of Sabah and Sarawak itself especially on the development. Therefore changes need to be made accordance with time. Some solutions are being recommended in this research including Federal funding for the state of Sabah and Sarawak and the Constitutional awareness among the citizen in Sabah and Sarawak.